Pigmentos fotossintéticos e índice SPAD como Descritores de intensidade do estresse por deficiência hídrica em cana-de-açúcar - Silva, Marcelo de Almeida [UNESP]; dos Santos, Claudiana Moura [UNESP]; Vitorino, Hermeson dos Santos [UNESP]; Rhein, Andressa Freitas de Lima [UNESP] (My University, 2014)
The objective of this study was to evaluate the responses of sugar cane subject to water stress by photosynthetic pigments (chlorophylls a, b, total a + b, ratio chlorophylls a/b and carotenoids) and verify the use of SPAD index as a cultivar differentiation tool. The experiment was carried out in a greenhouse, where four cultivars (IACSP95-5000, RB835054, RB928064 and SP80-3280) were grown in pots. After 65 days of planting, two treatments were implemented, i.e., with no stress (-D) and with water stress (D +). Cultivars of sugar cane respond differently in relation to photosynthetic pigments when subjected to water deficit. Cultivars IACSP95-5000 and RB928064 have less effect of drought, that is attributed to the ability of maintaining the chlorophyll and carotenoid content, as well as higher SPAD index values under this condition. Water stress affects with more intensity the cultivars RB835054 and SP80-3280 due to higher reductions in photosynthetic pigments and SPAD index. SPAD index is correlated with chlorophyll and carotenoid content in sugar cane and can be used as a technique for selecting tolerant cultivars to drought in breeding programs.
Photosynthetic pigments and spad index as Descriptors of water deficit stress intensity in sugar cane
Keywords: Carotenoids; Chlorophyll; Cultivars; Saccharum spp; Water stress